Pengaruh Debt To Equity Ratio (DER), Return On Assets (ROA) dan Return On Equity (ROE) terhadap harga saham pada perusahaan perbankan di Bursa Efek Indonesia periode 2016-2023 - Senjaya, Eka; Sumawidjaja, Riyandi Nur (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study aims to analyze the Debt to Equity Ratio, Return On Assets, Return On Equity, and Stock Prices of banking companies listed on the Indonesia Stock Exchange from 2016 to 2023, as well as to examine the impact of each ratio on Stock Prices. The research employs a quantitative method with a descriptive and verificative approach, using secondary data collected through documentation. The population consists of book 3 banks that experienced a decline in stock prices on the Indonesia Stock Exchange during the period, with a sample of 6 companies. The analysis includes descriptive statistics, classical assumption tests, multiple regression tests, and hypothesis testing both partially and simultaneously. The results show that the Debt to Equity Ratio tends to decline, Return On Assets and Return On Equity fluctuate, and Stock Prices tend to decrease. Additionally, the Debt to Equity Ratio and Return On Assets have a significant positive effect on Stock Prices, while Return On Equity has a significant negative effect. Overall, the three ratios have a significant positive impact on the Stock Prices of banking companies listed on the Indonesia Stock Exchange during the period.